CCSK Cert Prep: 2 Infrastructure Security for Cloud. - Lachance, Daniel (linkedin.com, 2021)
Learn how to secure cloud-based services as well as you would secure on-premises IT service environments and make progress in your preparations for the CCSK Cert Prep exam.